Arsenic sulfide enhances the therapeutic effect of hepatocellular carcinoma immunotherapy through STAT3-THBS1/CD47 pathway - Kang, Ting; Feng, Zhuowei; Cai, Yu; Huang, Ruizhe; Wang, Ruiheng; Liu, Zhiyi; Lu, Shumin; Xie, Shufeng; Liu, Han; Chen, Siyu (Frontiers in Immunology, 2025)
BackgroundHepatocellular carcinoma (HCC) represents a formidable challenge in oncology, with high mortality rates and limited therapeutic options, particularly for advanced-stage patients. While immunotherapy has shown promise, its efficacy in advanced HCC remains suboptimal, necessitating the exploration of more potent therapeutic strategies.MethodsThe HCC cell lines underwent treatment with arsenic sulfide and/or anti-PD1, while HepG2/Hepa1–6 cells were transduced with lentiviruses for THBS1 overexpression or knockdown. The MTT assay, FACS, Western blotting, qRT-PCR, and ChIP were employed to assess proliferation, modulation of proteins and genes. Additionally, C57BL/6J mice were utilized in vivo to investigate the ability of arsenic sulfide to enhance the efficacy of anti-PD-1 therapy.ResultsHere, we investigated the role of arsenic sulfide in HCC treatment and explored its potential synergistic effects and underlying mechanisms when combined with immunotherapy. First of all, using bioinformatics analysis and validation in vitro, we identified thrombospondin-1 (THBS1) as a key prognostic factor for HCC in Asian populations. Then, we demonstrated that arsenic sulfide inhibits HCC cell viability, induces apoptosis, and downregulates THBS1 expression. Furthermore, we observed that arsenic sulfide significantly enhances the anti-HCC effects of anti-PD-1 therapy. Mechanistic insights indicate that arsenic sulfide inhibits STAT3 phosphorylation, reduces THBS1 transcription, thereby disrupting the binding between tumor cell THBS1 and T cell CD47, consequently enhancing anti-PD-1 efficacy. Therefore, arsenic sulfide augments anti-PD-1 efficacy against HCC by inhibiting the STAT3-THBS1/CD47 pathway.ConclusionsCollectively, our findings elucidate the role of arsenic sulfide in conjunction with PD - 1 in HCC eradication and its underlying molecular mechanism, providing a precise scientific rationale and a robust theoretical basis for arsenic sulfide’s application in HCC treatment.